تحليل وقياس العلاقة بين تقلبات أسعار النفط و النمو الاقتصادي والبطالة في الجزائر للفترة 1990-2018 (مجلة الواحات للبحوث والدراسات, 2020)
This Study Aims To Measure And Analyze The Relationship Between Fluctuations In Oil Prices And Economic Growth And Unemployment In Algeria During The Period 1990-2018. Using The Vector Error Correction Model And Shock Response Functions, We Have Concluded That There Is A Causal Link Between The Price Of Oil, Economic Growth, And The Unemployment Rate. And That A Positive Shock In The Price Of Oil Will Have A Positive Impact On The Rate Of Growth And A Negative Impact On The Unemployment Rate In The Short And Long Term. Therefore, We Recommend That Economic Policymakers Need To Strengthen The Sources Of Economic Growth And Pursue An Economic Diversification Policy. Key Words: Oil Price, Unemployment, Economic Growth, Shock Response Functions